2020
DOI: 10.1186/s13039-020-0472-y
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal genetic analysis and differential pregnancy outcomes of two de novo cases showing mosaic isodicentric Y chromosome

Abstract: Background: Fetal cells collected from the amniotic fluid of two pregnant women indicated sex chromosome abnormalities. Therefore, we performed G-banded chromosome karyotype analysis, single nucleotide polymorphism array (SNP array), fluorescence in situ hybridization (FISH), and sequence-tagged sites (STS) analysis of the Y chromosome to determine the rare molecular genetics of the two fetuses. Case presentation: The karyotypes of the fetuses from patients 1 and 2 were mos 45,X[92]/46,X, +idic(Y)(q11.21)[8] a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…We further screened for chromosomes with CNVs which accounted for more than 5% which yielded chromosomes 2, 3, 5, 10, 11, and Y, indicating that there may be important gene fragments affecting spermatogenesis. A large number of genes on the Y chromosome have been confirmed to cause spermatogenesis arrest, while autosomal gene abnormalities have rarely been reported (16)(17)(18). In this experiment, 132 genomic CNVs were found in the 5 autosomal chromosomes 2, 3, 5, 10, and 11, including 8 deletions and 124 repeats.…”
Section: Discussionmentioning
confidence: 74%
“…We further screened for chromosomes with CNVs which accounted for more than 5% which yielded chromosomes 2, 3, 5, 10, 11, and Y, indicating that there may be important gene fragments affecting spermatogenesis. A large number of genes on the Y chromosome have been confirmed to cause spermatogenesis arrest, while autosomal gene abnormalities have rarely been reported (16)(17)(18). In this experiment, 132 genomic CNVs were found in the 5 autosomal chromosomes 2, 3, 5, 10, and 11, including 8 deletions and 124 repeats.…”
Section: Discussionmentioning
confidence: 74%
“…These results suggest that the phenotype of fetuses/neonates in whom idic(Y)/i(Y) is prenatally identified is usually that of a male with normal development, ascertained in the absence of indicators of a fetal structural anomaly. There are many cases of prenatally identified normal male phenotypes, but cases of prenatally identified normal female phenotypes with idic(Y)/i(Y) are extremely rare [ 23 , 44 , 49 , 51 , 58 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that the frequency of ‘both duplications and deletions of q11.223 ’ was higher compared with other regions in azoospermia patients, suggesting that q11.223 has a greater impact on sperm function, resulting in reduced spermatogenesis. q11.223 partially overlaps regions between AZFb and AZFc; q11.223 contains PRY, PRY2 and RBMY family genes, which are required for spermatogenesis (He et al., 2020). Loss of these spermatogenesis‐related genes frequently causes infertility, thus making an AZF deletion one of the leading genetic factors in SF.…”
Section: Discussionmentioning
confidence: 99%